(3EjSGZhLjs - (3GdCHgQj GdSeQbfOj, CKjQ GdOjf, GdeaVd Hf YeQ GdeaVd, J (B663 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3EjSGZhLj GddaX GdOGd Ydi eG hVY dg HGdeWGHbI Ch Ydi LQjg HGdJVejf Ef cGf dg CLRGA hYdi eG jdGReg aj GdPgf HGdGdJRGe cGdEfSGf aEfg jOd Ydi GdMjhGf GdfGWb HGdeWGHbI hYdi CMOgeG HGdJVejf hYdi bGHd GdYde (B...s
(3BNQgG (B:s
.. (3hWHY eSJbje dG jMJGL Edi QO Tcd GdKGfj Edi GdChd hGdKGdK jQJO Edjg HYcS GdUZQi hGdQGHY jQJO Edjg HYcS GdJQJjH Ch HYcS Ch HYcS GdebOeJjf LejYG hEfeG jfJL GdKGfj YfO GNJdGa ebOeJg hGdGYLGH (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/279s
(3cTa GdXfhf (B1/206s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs